A Solution‐Processable (Tetraaniline‐b‐Polyethylene Glycol)3 Star‐Shaped Rod‐Coil Block Copolymer with Enhanced Electrochromic Properties. Issue 4 (14th December 2015) - Cao, Linyu; Gong, Chen; Yang, Jiping
Abstract : A novel electroactive star‐shaped rod‐coil copolymer composed of a benzene core and three symmetrically positioned tetraaniline‐b‐poly(ethylene glycol) arms, (TAni‐ b ‐PEG)3 rod‐coil block copolymer, is synthesized successfully and characterized using Fourier transform infrared spectroscopy (FTIR), UV–vis, 1 H NMR, and matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry. Uniform and high‐quality (TAni‐ b ‐PEG)3 thin films onto indium tin oxide‐coated glass surface are fabricated simply from its DMF solution. Resulting (TAni‐ b ‐PEG)3 copolymer thin films possess excellent electrochromic properties with a high optical contrast of 73.3%, superb coloration efficiency of 318.5 cm 2 C −1 at 750 nm. Very short switching times, that is, 2.11 s and 2.14 s for coloring and bleaching times, respectively, are observed as well. The mechanism of these impressive electrochromic properties of (TAni‐ b ‐PEG)3 thin films possessed is proposed based on the atomic force microscopy investigation, star‐shaped molecular geometry, synergetic electronic and ionic conductivity and amphiphilic self‐assembly feature of (TAni‐ b ‐PEG)3 copolymer, which can self‐assemble to form cylinder pattern consisting of quick pathways for electronic charges and ionic species, respectively. Abstract : A novel electroactive star‐shaped rod‐coil block copolymer with three symmetrically positioned tetraaniline‐ b ‐polyethylene glycol arms ((TAni‐ b ‐PEG)3 ) is reported. Due to the star‐shaped molecular geometry, synergetic electronic and ionic conductive capability, and amphiphilic self‐assembly feature, solution‐casting (TAni‐ b ‐PEG)3 thin films possess excellent electrochromic features with high optical contrast of 73.3%, superb coloration efficiency of 318.5 cm 2 C −1, and short coloring and bleaching times of ≈2 s.